Role play to alleviate speaking anxiety: Action research in ESP class of Batam Tourism Polytechnic - Maldin, Siska Amelia; Sianipar, Baktivillo (CAHAYA PENDIDIKAN, 2025)
This study analyzes the effectiveness of the role-play technique as a pedagogical intervention to reduce speaking anxiety among students in the English for Specific Purposes (ESP) course at Batam Tourism Polytechnic. Considering the significance of English proficiency in the hospitality industry, the research aims to enhance students’ confidence and communicative competence through interactive learning methods. The study employed a Classroom Action Research (CAR) design with a mixed-methods approach to gain a comprehensive understanding of the impact of role play. A total of 23 students participated as the sample of this research. Data were collected using speaking performance rubrics, observation checklists, field notes, and a speaking anxiety questionnaire adapted from Horwitz's Foreign Language Classroom Anxiety Scale (FLCAS). Oral test results indicated that 91.30% of students met the minimum mastery criteria, with 21 out of 23 students passing. Post-intervention data showed that 40% of students experienced low anxiety, while 60% were categorized as having moderate anxiety. These findings suggest that role play effectively reduces speaking anxiety and improves oral proficiency in an ESP context. It is recommended that structured role-play activities be integrated consistently within extended learning hours to maximize engagement and language practice.